Soluble α-Klotho Serum Levels in Chronic Kidney Disease. (19th March 2015) - Rotondi, Silverio; Pasquali, Marzia; Tartaglione, Lida; Muci, Maria Luisa; Mandanici, Giusy; Leonangeli, Cristiana; Sales, Silvia; Farcomeni, Alessio; Mazzaferro, Sandro
Abstract : Transmembrane α -Klotho (TM-Klotho), expressed in renal tubules, is a cofactor for FGF23-receptor. Circulating soluble- α -Klotho (s-Klotho) results from TM-Klotho shedding and acts on Phosphate (P) and Calcium (Ca) tubular transport. Decreased TM-Klotho, described in experimental chronic kidney disease (CKD), prevents actions of FGF23 and lessens circulating s-Klotho. Thus, levels of s-Klotho could represent a marker of CKD-MBD. To evaluate the clinical significance of s-Klotho in CKD we assayed serum s-Klotho and serum FGF23 in 68 patients (age58 ± 15 ; eGFR45 ± 21  mL/min). s-Klotho was lower than normal (519 ± 183 versus845 ± 330  pg/mL, P < . 0001 ) in renal patients and its reduction was detectable since CKD stage 2 (P < . 01 ). s-Klotho correlated positively with eGFR and serum calcium (Cas) and negatively with serum phosphate (Ps), PTH and FGF23. FGF23 was higher than normal (73 ± 51 versus36 ± 11, P < . 0002 ) with significantly increased levels since CKD stage 2 (P < . 001 ). Our data indicate a negative effect of renal disease on circulating s-Klotho starting very early in CKD. Assuming that s-Klotho mirrors TM-Klotho synthesis, low circulating s-Klotho seems to reflect the ensuing of tubular resistance to FGF23, which, accordingly, is increased. We endorse s-Klotho as an early marker of CKD-MBD.